THE RELATIONSHIP BETWEEN SOCIAL MEDIA AND PARTICIPATORY CITIZENSHIP SKILLS: A BIBLIOMETRIC REVIEW - Khofifah Ajeng Triani; Kokom Komalasari; Iim Siti Maysitoh; Amiza Rezika (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article examines the relationship between social media and participatory citizenship skills through a bibliometric and qualitative literature review approach. The study analyzed 120 articles published between 2021 and 2025 and indexed in the Scopus database. Literature selection was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) procedure, while bibliometric mapping was performed using VOSviewer to identify major research themes, keyword networks, and intellectual structures within the field. The findings reveal that the knowledge structure of social media and participatory citizenship is organized into four major clusters: conceptual, pedagogical, participatory-political, and methodological. The analysis shows that digital citizenship extends beyond technical digital skills and encompasses ethical, critical, and reflective competencies required for responsible engagement in digital environments. Social media has expanded opportunities for civic participation by facilitating communication, collaboration, and collective action; however, it also introduces challenges such as misinformation, polarization, and superficial forms of engagement. These findings suggest that citizenship education should move beyond knowledge transmission toward the development of participatory competencies supported by digital literacy, awareness of digital rights and responsibilities, and the cultivation of healthy digital cultures. This study contributes a conceptual framework for understanding how meaningful, measurable, and responsible citizen participation can be fostered in the digital era.